PENGGUNAAN BAHASA INDONESIA PADA SURAT DINAS DI KANTOR KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Yulandari, Tiara; Muzammil, Ahmad Rabi ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Research on the use of language in official letters at the Pemangkat District office in Sambas City focuses on the use of language in letters issued by the government of Pemangkat District. The use of the language in question is the Indonesian Spelling, diction, and effective sentences used in outgoing letters in May, June, and July 2018. The focus is in accordance with the formulation of the problem directly related to the research objectives, namely: (1) Describe the use of Indonesian Spelling on official letters in the pemangkat sub-office, (2) Describing the use of diction on official letters in the pemangkat sub-office, (3) Describing the use of effective sentences in official letters in the Pemangkat sub-district office, and (4) describing plans for implementing research results about official letters and class VII Indonesian language learning based on the 2013 curriculum.This research uses descriptive method and is in the form of qualitative. The data of this study are written on a letter issued by the government of Pemangkat District. The data source of this research is the letter out of Pemangkat District office in May, June, and July 2018. Data collection techniques used in this study are documentation techniques.Â Keywords: Official Letters, Indonesian Spelling, Dictation, Effective Sentences, Pemangkat District.